SANCTIONS DE L’ASSEMBLEE PROVINCIALE DES IRREGULARITES BUDGETAIRES EN PROVINCE ORIENTALE (RDC) DE 2007 A 2015 - LIMENGO , Dieudonné BARUTI; Clément ATSIDRI YILA (IJRDO - Journal of Business Management, 2019)
In the diagram of control of the execution of finance edicts, the political control operated by the provincial assembly holds in principle the first rank. Having allowed initially carrying out of operations of returns and expense, it follows the control of it by the provincial assembly and budgetary irregularity sanctions. Sanctions of the budgetary irregularities of the provincial assembly make part of the most important attributes of the provincial deputies in democracy. If it allows the provincial Government to give account of its management to the elected of the people, it is one of indicators of the strength of the provincial assembly. However, in Oriental Province, the assessment of the role of the provincial assembly must be placed in the context of a political institution undergoing various constraints. Practices of mistrust motion proved to be rich in revival but didn’t lead to the discounted results. This weak application of sanction had repercussions on the governance of the Oriental Province at particular the financial waste, the weakening of the provincial assembly and the under - development of the Province Oriental.